(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
This article aims at examining abortion rights in Ireland, by analysing the historical premises of the discourse and the most recent law reform, offering a bioethical reading of the issue. The peculiar geographical context considered allows to highlight how Northern Ireland’s experience of abortion rights can be deemed as complementary to the Republic of Ireland’s one. In this article, the core focus is dedicated to the peculiar relation between morality and health in relation to abortion rights in Ireland.